PERAN BADAN KERJASAMA ANTAR DESA DALAM PERLINDUNGAN, PENGELOLAAN, PELESTARIAN HASIL PELAKSANAAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI KABUPATEN BANYUASIN - Holipah, Holipah (STISIPOL Pahlawan 12 Press, 2024)
This studies audit modified into carried out to find out the general safety, manage, and conservation efforts that had been carried out to provide criminal guarantees, preserve sustainability, and increase the outcomes of the participatory trends that have been set up via PNPM and facilitated thru the guarantees). The trouble confronted thru BKAD is that it is a sustainable arrears from the SPP group in Banyuasin. This studies takes up the issue via the use of investigating the location of BKAD in defensive, coping with, and keeping the consequences of the implementation of PNPM in Banyuasin. The qualitative qualitative technique have become selected to study the trouble this is being investigated. The research statistics had been amassed through in-intensity interviews, observations, and documentation. The self-discipline of informants was done with the aid of way of purposive sampling and snowball sampling. Records is verified via regular participation, declaration, member checking, and triangulation. The information had been analyzed qualitatively, which consisted of facts collection, facts reduction, data presentation, and statistics verification. The research findings cowl three problems. First, BKAD takes safeguards aimed at inventorying SPP assets and properties through discussions. 2nd, BKAD carries out a manage software by using manner of restructuring consumer loans, taking element with all the corporations worried in PNPM. 0.33, the conservation efforts completed with the aid of using BKAD have resulted in sustainable SPP.